Head and neck osteosarcomas - A review of the literature - Ademar Takahama Junior; Fábio de Abreu Alves; Clóvis Antonio Lopes Pinto; André Lopes Carvalho; Luiz Paulo Kowalski; Márcio Ajudarte Lopes (Universidade Estadual de Campinas, 2015)
Osteosarcoma (OS) is a rare and aggressive malignant bone tumor, which occurs more frequently in long bones of young people. About 10% of the cases affect the head and neck region presenting peculiar features. The main sites of this tumor in head and neck are the mandible followed by the maxilla, and it seems to have a similar distribution between the genders. The most common clinical feature is the local swelling. Pain and paresthesia may be present in some cases. The early signs of this tumor in the jaw bones can be a dental mobility or widening of the periodontal ligament space. The diagnosis of OS is established with histological examination, which shows malignant mesenchymal cells producing osteoid or bone. The main modality treatment for head and neck OS is surgical resection with wide margins. The benefits of adjuvant therapies like chemotherapy and radiotherapy are still not clear. The major complication is local recurrence, with metastasis occurring as a solitary or a late stage event.